Sobre o negacionismo no ciberespaço : a "enciclopédia alternativa" Metapedia e sua proposta de educação histórica - Silva, Diego Leonardo Santana (2017)
This work analyzes the Metapedia portal (www.metapedia.org), which is an initiative from right-wing extremists groups, and its proposal to be an Alternative Encyclopedia. The Metapedia is an electronic encyclopedia which adopts the Wiki system and has as an objective to be an electronic support. In presenting concepts and biographies, Metapedia uses negationist revisionism as its basis, offering different versions for events and historical concepts, especially those related to World War II. In the research we selected entries on this portal as sources. They were analyzed with the intention of exposing what kind of “history” is told in Metapedia. The dissertation was organized in sections that covered the structure and proposal of Metapedia to demonstrate how it works, besides performing the analysis of fundamental entries to the Portal. With this, we offer a comprehensive view on this proposal of encyclopedia in the digital environment. We consider that Metapedia is embedded in the context of history rewriting activities on the World Wide Web, at the position of a pedagogical support of intolerance in the digital environment. The research found that, although it fulfills its objective of being a pedagogical support according to its idealizers, in part, Metapedia does not show success in its proposal to encourage the debate on the subjects that it intends, since its foundation, to review.